Pengaruh Lingkungan Bisnis Dan Keterampilan Kewirausahaan Terhadap Kinerja Bisnis - Faza, Muhammad Fernanda Maulana; Solihin, Ismail (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of MSMEs that are able to survive and develop in advancing regional and national economic levels has become an interest for the government in supporting and promoting these business actors so that they continue to contribute to improving national development. This research aims to determine the influence of the business environment and entrepreneurial skills on the business performance of MSMEs in the fashion sector of Bandung City. This research data is primary data, namely data from questionnaires distributed to respondents. The population in this study was 907 MSMEs in the fashion sector in Bandung City and a sample of 100 MSMEs was taken based on the Slovin formula calculation. The analytical method used is multiple regression analysis. The research results show that there is a positive influence of the business environment on the business performance of MSMEs, there is a positive influence of entrepreneurial skills on the business performance of MSMEs.